2021
DOI: 10.1021/jacs.0c11978
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically Tuning the Photodissociation of the Irgacure 2959 Photoinitiator in the Gas Phase by Cation Binding

Abstract: The low-lying electronic states of Irgacure 2959, a Norrish-type I photoinitiator, complexed with a single metal cation are investigated in the gas-phase by photodissociation action spectroscopy. Analysis of the band-shifts using quantum chemical calculations (TD-DFT and SCS-CC2) reveals the underlying influence of the charge on the key electronic energy levels. Since the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…To our knowledge, our study of the effect of alkali metal complexation on oxybenzone is the first to directly probe how cation binding can affect the photodynamics of a sunscreen molecule. However, our results were mirrored by other subsequent studies where metal cation binding has been reported to significantly perturb the excited-state behaviour of an aromatic molecule ( Marlton et al, 2021 ; Robertson et al, 2021 ), indicating that cation coordination may have widespread photochemical importance.…”
Section: Sodium Cation Binding Can Disrupt Sunscreen Actionsupporting
confidence: 85%
“…To our knowledge, our study of the effect of alkali metal complexation on oxybenzone is the first to directly probe how cation binding can affect the photodynamics of a sunscreen molecule. However, our results were mirrored by other subsequent studies where metal cation binding has been reported to significantly perturb the excited-state behaviour of an aromatic molecule ( Marlton et al, 2021 ; Robertson et al, 2021 ), indicating that cation coordination may have widespread photochemical importance.…”
Section: Sodium Cation Binding Can Disrupt Sunscreen Actionsupporting
confidence: 85%
“…Increasing equivalents of Mg 2+ ions appear to extend the absorption via the 1 ππ* band to longer wavelengths, ultimately eclipsing the 1 nπ* band contribution. Drawing on the gas-phase cluster studies of Marlton et al, we attribute this phenomenon to stabilization of the 1 ππ* state by coordination of a Mg 2+ cation to the ACP carbonyl group. From these observations, the excitation wavelengths (λ exc ) selected for TEAS experiments were 280 and 320 nm to compare excited-state dynamics following UV absorption in the 1 ππ* and 1 nπ* bands and to explore the effects of metal-ion coordination on the ultrafast photochemistry of ACP.…”
mentioning
confidence: 76%
“…They were also able to demonstrate the preferential photoexcitation of benzophenone molecules transiently hydrogen-bonded to phenol co-solute molecules, thereby enhancing the rate of bimolecular reaction beyond the diffusional limit . Coote and co-workers used TD-DFT calculations to show that coordinated Lewis acids can tune excited-state energy levels in Irgacure 2959, a commercially available ACP derivative. ,, This mechanism was validated experimentally by using several different metal ions to establish orientated electric fields (OEFs) in gas-phase complexes . Similarly, externally applied electric fields have been shown to drive reaction pathways that would otherwise be energetically unavailable, , and triplet excited-state reordering has been observed for ACP derivatives embedded within zeolite pores containing metal ions .…”
mentioning
confidence: 93%
“…Importantly, PDAS yields a powerful assessment of photochemical reactivity of individual components, even in crude mixtures, and is thus potentially compatible with combinatorial chemistry and multicomponent reactions. These synthetic approaches are not readily amenable to analogous solution-phase analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, UV photodissociation action spectroscopy (PDAS) is employed on an ion-trap mass spectrometer coupled to a tunable laser system to evaluate the wavelength dependence of nitrile imine formation from substituted tetrazoles. Combining the analytical benefits of spectroscopy and mass spectrometry, the resulting action spectra reveal absorption events that produce a specified molecular mass change, which can guide the design of new substrates with desirable photodissociation profiles . We show that the efficiency of nitrile imine formation as a function of irradiation wavelength can be readily surveyed in the gas phase, independent of dipolarophile cycloaddition.…”
Section: Introductionmentioning
confidence: 96%